Is educational attainment associated with young adult cardiometabolic health? - Grace A. Noppert; Lauren Gaydosh; Kathleen Mullan Harris; Andrea Goodwin; Robert A. Hummer (Elsevier, 2021)
Educational disparities in health and mortality are well-documented and evidence suggests that they may be widening. Yet, there is much unknown about when educational disparities begin to emerge and for whom. This paper investigates the association between educational attainment and cardiometabolic health in young adults with critical attention paid to differences across racial/ethnic and sex subgroups. We focus on cardiometabolic health in young adulthood as it is particularly relevant for understanding current population health trends. We used data from the National Longitudinal Study of Adolescent to Adult Health (Add Health) when participants were aged 12-19 years (Wave I) and aged 24-32 years (Wave IV). Using a series of logistic regression models, we first estimated the association between education and five markers of cardiometabolic health (high-risk blood pressure, high-risk waist circumference, diabetes/pre-diabetes, hyperlipidemia, and high-risk inflammation). We then examined the extent to which this association was explained by adolescent health and both adolescent and young adult socioeconomic status (SES) (including parental education, participant educational attainment, household income, and employment status). Finally, we investigated whether the association between educational attainment and cardiometabolic health differed by race/ethnicity and sex. We found evidence of an association between educational attainment and cardiometabolic health that persisted net of adolescent health, adolescent SES, and young adult SES. We also found some evidence of modest differences in this association by race/ethnicity and sex. Our findings suggest that even as early as young adulthood there are disparities in cardiometabolic health by educational attainment, which may lead to even larger disparities in late life health.